Risk Factors Affecting the Incidence of Diarrhea in Children Under Five Years Old in the Working Area of Tarus Public Health Center, Kupang District, in 2022 - Maria Veronika Tonny; Sigit Purnawan (Universitas Nahdlatul Ulama Surabaya, 2023)
Diarrhea is a disorder of defecation characterized by defecation more than 3 times a day with the consistency of liquid stool, may be accompanied by blood. Until September 2022 Puskesmas Tarus had the highest incidence of diarrhea compared to other health centers with 126 cases of diarrhea in toddlers. The purpose of this study was to determine the risk factors associated with the incidence of diarrheal disease in children under five years of age in the working area of Puskesmas Tarus, Kupang Regency. This study was an analytic observational study using a case control study research design. This study was conducted in the working area of Puskesmas Tarus Kupang Regency in February-March 2023. The results showed a significant relationship between maternal knowledge (p=0.000; OR=3,974), maternal attitude (p=0.000; OR=4,594), hand washing behavior (p=0.000; OR=4,421), exclusive breastfeeding history (p=0.001; OR=3,632) and maternal education (p=0.023; OR=2,400) with the incidence of diarrhea in toddlers. There is no significant relationship between maternal employment status and the incidence of diarrhea in toddlers (p=0,114; OR=0,489). Conclusion, that the variables of maternal knowledge, maternal attitude. hand washing behavior, exclusive breastfeeding history and maternal education have a significant relationship with the incidence of diarrhea in toddlers, and the variable maternal employment status has no significant relationship with the incidence of diarrhea in toddlers in the working area of Puskesmas Tarus, Kupang Regency.